Glycation, carbonyl stress and AGEs inhibitors: a patent review. (2nd November 2015) - Jahan, Humera; Choudhary, M Iqbal
Abstract : Introduction: The glycation process, comprising a series of reactions, results in the formation of heterogeneous adducts, known as advanced glycation end products (AGEs). AGEs are involved in several pathologies, including diabetes-associated late complications, atherosclerosis, Alzheimer's disease and inflammatory arthritis. Several inhibitors of AGEs and/or reactive carbonyl species have been identified from various sources, including natural products and synthetic molecules, and have been investigated for their mechanism of action. Areas covered: This review covers the literature on AGEs inhibitors published as patents between 2001 and 2014. Initially, the earlier reported molecules with AGEs inhibitory properties, their mechanism of actions and reported adverse effects are discussed. The main focus has been on the chemical structures, methods for evaluation of the activity, modes of action, pharmacokinetics and therapeutic outcomes. The potential of these AGEs inhibitors in the treatment and management of a number of diseases are also discussed in this review. Expert opinion: The reactive carbonyl species and AGEs have recently emerged as novel therapeutic targets for the prevention and treatment of several diseases. Currently, the major concerns with the use of AGEs inhibitors as therapeutic agents are low effectiveness, poor pharmacokinetics and undesirable side effects. Many of the AGEs inhibitors reviewed here possess potent antiglycation activity and are devoid of undesirable side effects. These small molecules inhibitors can, therefore, serve as scaffolds for the development and designing of new AGEs inhibitors as clinical agents.